2012
DOI: 10.1016/j.neurobiolaging.2011.09.035
|View full text |Cite
|
Sign up to set email alerts
|

The age-related deficit in LTP is associated with changes in perfusion and blood-brain barrier permeability

Abstract: In view of the increase in the aging population and the unavoidable parallel increase in the incidence of age-related neurodegenerative diseases, a key challenge in neuroscience is the identification of clinical signatures which change with age and impact on neuronal and cognitive function. Early diagnosis offers the possibility of early therapeutic intervention, thus magnetic resonance imaging (MRI) is potentially a powerful diagnostic tool. We evaluated age-related changes in relaxometry, blood flow, and blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 53 publications
4
71
0
Order By: Relevance
“…Interestingly, increased expression of these chemokines has been reported in AD (Tripathy et al, 2007(Tripathy et al, , 2010Xia et al, 2000), whereas increased T cell expression of CCR5 and CXCR2 has also been reported (Liu et al, 2010;Man et al, 2007;Reale et al, 2008). Infiltration of immune cells may also be a consequence of increased bloodebrain barrier permeability, which we have observed in aged animals (Blau et al, 2012) and APP/PS1 mice (Minogue et al, unpublished), and which is known to occur after B. pertussis infection (Linthicum et al, 1982).…”
Section: Discussionsupporting
confidence: 51%
“…Interestingly, increased expression of these chemokines has been reported in AD (Tripathy et al, 2007(Tripathy et al, , 2010Xia et al, 2000), whereas increased T cell expression of CCR5 and CXCR2 has also been reported (Liu et al, 2010;Man et al, 2007;Reale et al, 2008). Infiltration of immune cells may also be a consequence of increased bloodebrain barrier permeability, which we have observed in aged animals (Blau et al, 2012) and APP/PS1 mice (Minogue et al, unpublished), and which is known to occur after B. pertussis infection (Linthicum et al, 1982).…”
Section: Discussionsupporting
confidence: 51%
“…Astrocyte proliferation: Increased number and size GFAP expression: Increased Rodriguez-Arellano et al, 34 Harris et al 37 Chisholm and Sohrabji, 38 Middeldorp 69 Blau et al 69 Lucke-Wold et al 75 Lucke-Wold et al, 75 Cerbai et al 76 Buschini et al 77 Alzheimer's disease such as vascular-mediated Ab-independent neurodegeneration, regulation of Ab clearance and contributions to tau pathology, neuronal loss and cognitive decline. 93 Pericytes demonstrate large numbers of intracellular inclusions, pinocytotic vesicles, large lipid granules and mitochondrial abnormalities suggesting cellular dysfunction and/or degeneration.…”
Section: Astrocytesmentioning
confidence: 99%
“…This close relationship between plasticity and cerebral blood flow is illustrated in studies showing that declines in brain perfusion (e.g. aging, artificially induced models) affect LTP (224)(225)(226). As such, the beneficial effects of flavonoids might be particularly relevant to alleviate or prevent declines in vascularization of the brain and as such preserve synaptic function and cognitive abilities in aging and neurological disease.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 95%